Alimentos ultraprocessados estão associados a fatores psicossociais em mulheres com disfunção temporomandibular muscular crônica? um estudo transversal - Fontoura, Luana Pinheiro Guerra (2024)
he high consumption of ultra-processed foods (UPF) has been associated with the increase of non-communicable chronic diseases in the globalized world, demonstrating that dietary quality assessment should not be limited to nutrient adequacy but also consider the extent of industrial processing. This study is an analytical cross-sectional clinical study aimed at evaluating and comparing the participation of NOVA food classification groups in the diet of women with temporomandibular disorder (TMD) of chronic myalgia type and asymptomatic women, as well as assessing the association between UPF consumption and covariates of body mass index (BMI), ultra-sensitive C-reactive protein (us-CRP) levels, and psychosocial factors in the TMD group. The sample consisted of 68 women for the TMD group and 16 for the asymptomatic group. Dietary records were obtained through three 24-hour dietary recalls (R24h), where all food items consumed were classified according to the NOVA classification system into mean percentage (%Kcal/d) of: (I) unprocessed or minimally processed foods; (II) processed culinary ingredients; (III) processed foods; and (IV) UPF. Additionally, for the TMD group, UPF participation was divided into consumption quintiles to evaluate the association with BMI, us-CRP, Hospital Anxiety and Depression Scale (HAD), Pain Catastrophizing Scale (B-PCS), and Pittsburgh Sleep Quality Index (PSQI). Statistical analyses were conducted using t-tests for independent samples, Mann-Whitney tests, Pearson's chi-square tests, ANOVA, and Tukey's post hoc tests. SPSS 25.0 software was used, with a significance level set at p<0.05. There was no difference in the participation of NOVA groups between women with TMD and asymptomatic women, with mean percentages of: (I) 41% and 45%; (II) 10% and 10%; (III) 13% and 11%; and (IV) 36% and 32%, respectively. For the TMD group, increased quintiles of UPF dietary participation were associated with higher BMI, greater risk of anxiety, depression, pain catastrophizing, and poor sleep. Therefore, although the dietary participation of the four NOVA food groups is similar for women with TMD and asymptomatic women, higher consumption of UPF was associated with psychosocial impairment in the TMD group.